(3GdJMQjQ aj GdaQhYs - (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s
(3ChdgG (B:s
(3efg heGdG jJWgQ Hg Ydi MGd EeG Cf jLGhQg Ch jNGdWI aNGdWI s
(3BNQgG (B:s
(3aEf cGf bO CSde bHd Cf jYJb HYO eG GYJb Ke dMb HOGQ GdMQjI s
(3jfbU hQbI (B74s
94 (3ef GdJUhjQs
(3hgh hba GdCejQ GdeJhcd HecJHI LGeY UfYGA (B1343(3g` GdfSNI HGgJI hJefY GdQhjI ai cKjQkG efgGs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3eJaQbGJs